The impact of Type 2 diabetes prevention programmes based on risk‐identification and lifestyle intervention intensity strategies: a cost‐effectiveness analysis. Issue 5 (10th March 2017) - Breeze, P. R.; Thomas, C.; Squires, H.; Brennan, A.; Greaves, C.; Diggle, P. J.; Brunner, E.; Tabak, A.; Preston, L.; Chilcott, J.
Abstract: Aims: To develop a cost‐effectiveness model to compare Type 2 diabetes prevention programmes targeting different at‐risk population subgroups with a lifestyle intervention of varying intensity. Methods: An individual patient simulation model was constructed to simulate the development of diabetes in a representative sample of adults without diabetes from the UK population. The model incorporates trajectories for HbA1c, 2‐h glucose, fasting plasma glucose, BMI, systolic blood pressure, total cholesterol and HDL cholesterol. Patients can be diagnosed with diabetes, cardiovascular disease, microvascular complications of diabetes, cancer, osteoarthritis and depression, or can die. The model collects costs and utilities over a lifetime horizon. The perspective is the UK National Health Service and personal social services. We used the model to evaluate the population‐wide impact of targeting a lifestyle intervention of varying intensity to six population subgroups defined as high risk for diabetes. Results: The intervention produces 0.0003 to 0.0009 incremental quality‐adjusted life years and saves up to £1.04 per person in the general population, depending upon the subgroup targeted. Cost‐effectiveness increases with intervention intensity. The most cost‐effective options are to target individuals with HbA1c > 42 mmol/mol (6%) or with a high Finnish Diabetes Risk (FINDRISC) probability score (> 0.1). Conclusion: The model indicates that diabetes prevention interventions are likely to be cost‐effective and may be cost‐saving over a lifetime. In the model, the criteria for selecting at‐risk individuals differentially impact upon diabetes and cardiovascular disease outcomes, and on the timing of benefits. These findings have implications for deciding who should be targeted for diabetes prevention interventions. What's new?: We describe the first study to compare the cost‐effectiveness of a lifestyle intervention to prevent diabetes across different high‐risk population subgroups and over different intervention intensities. We find that diabetes prevention programmes are cost‐effective over a lifetime horizon, regardless of risk criteria or intervention intensity. Our study estimates that a lifestyle intervention will have a differential impact on disease outcomes (diabetes vs. cardiovascular disease) and the time horizon of cost savings in different high‐risk groups. These findings should help policymakers decide their objectives in developing suitable criteria for diabetes prevention programme content and eligibility.